Analysis of narrative text “wooden chess with the blue elder icon” - Ganbaatar, Nandinbileg (Studia Folclorica, 2024)
The article analyzes and defines the genre of the narrative text “Wooden chess with the blue elder icon” which is directly related to the 100-station folk chess of the ancient Mongols. It was inherited among the descendants of the Uriankhans in the Daichin Zasag Hoshuu of Zasagt Khan Province. In this unique story, before the creation of land and water, the Sun created the Earth by transporting dirt from Bumba’s land and the Moon sacrificed water from the land of the Gods and created the four oceans by sending rain, and the Sun and the Moon brought water from Zuidelgui land and dispersed it into the sky where it manifested as rain that created the four oceans, the Sun and Moon swore an oath in front of the Heavens at the feast of Khurmast that they would become the Lord of the Earth, where the sun would protect the earth in the day and the moon would in the night so that the Mother Earth was living in peace for nine billion years, a period called the feast, then suddenly from a distant foreign continent demons invaded to seize the Earth in a period known as the ruin, The Heavens intervened in the war as mankind, the sun, and moon were on the brink of defeat, expelling the demons from the Earth, from there, to retain the knowledge of the war with the demons, the Sun, Moon, and the Heavans created chess. For this reason there are white and black sides to chess to develop man’s intelligence. From this we conclude that “Wooden chess with the blue elder icon” is not a heroic epic but rather a myth where the power of the Heavens are greater than that of mankinds. The first three chapters of this story are related to the mythology of the origin of the world, while the last three chapters are the mythological version of the origin chess. “Хөх өвгөн сахиустай хөл модон шатрын тууль” хэмээх аман бичвэрийг шинжлэх нь Хураангуй: Тус өгүүлэлд хуучин “Засагт хан аймгийн Дайчин засгийн хошууны урианхануудын үр хойчсын дунд өвлөгдөж ирсэн эртний монголчуудын аравтын системийг санагдуулам 100 буудалт шатартай шууд холбогдох “Хөх өвгөн сахиустай хөл модон шатрын тууль” хэмээх шинэхэн олдоод буй аман зохиолын жишээг задлан шинжилж, төрөл зүйлийг судлан тогтоохыг зорьсон болно. Тус өвөрмөц туурвилд газар ус үүсэхийн өмнө Наран Бумбын орноос шороо атган авч газар дэлхийг бүтээсэн тухай, Саран зүйдэлгүй орноос усыг завьяалан дээжилж, хур бороо оруулснаар дөрвөн далайг бүтээсэн тухай, Хурмастын найр дээр Тэнгэр нарын өмнө Наран Саран хоёр тангараг тавин, энэ газар дэлхийн эзэн сахиул болсон тухай, эх болсон газар ерэн дүнчүүр насыг хурааж энх амгалан оршиж байтал харь тивийн хий барам халдан эзэлсэн муу цаг ирсэн тухай, Тэнгэр нар харь тивийн муу бармуудыг хөөж газар дэлхийг аварсан тухай, мангас дайсны аюулыг мартахгүй санаж байг гэж тэнгэр эрхсээс шатар бүтээж өгсөн тухай, монгол шатрын жаягийн тухай, шатрын андгай тангаргийн тухай өгүүлж байна. Бидний үзэхээр энэхүү “Хөх өвгөн сахиустай хөл модон шатрын тууль”-ийн эхний гурван бүлэг нь ертөнцийн үүслийн домог зүйтэй холбогдож байгаа бол сүүлийн гурван бүлэг нь шатар үүссэн тухай соёлын үүслийн домог зүйн жишээ мөн байна. Түлхүүр үг: Монгол аман зохиол, миф-эртний домог, баатарлаг туульс, шатар